Kajian Etika Profesi Apoteker dalam Penjualan Antibiotik Tanpa Resep Dokter dalam Perspektif Islam - Novita Diana Ayu Candra; Oman Fathurohman SW (An-Najat, 2025)
The sale of antibiotics without a doctor's prescription is a serious problem in Indonesia which has an impact on increasing antimicrobial resistance. This study aims to examine the ethics of the pharmacist profession in selling antibiotics without a doctor's prescription from the perspective of Islamic. The method used is a literature-based juridical-normative study. The results of the study indicate that the main factors that encourage violations in the sale of antibiotics without a doctor's prescription are the permissive attitude of pharmaceutical personnel, beliefs formed from personal experience, and weak law enforcement. From the perspective of Islam, this behavior is compared with the Qur'an and As-Sunnah, namely the values ​​of trust, integrity, and prophetic work ethic. Pharmacists are expected not only to carry out their duties in accordance with applicable legal provisions, but also to integrate moral values, social responsibility, and Islamic ethics in every aspect of their professional services.